Aproximación a las fuentes de los derechos del hombre y del ciudadano: Notas sobre las fuentes filosóficas y jurídicas de la1 Declaración de 1789 (2012)
The 1789 Declaration of the Rights of Man and of the Citizen is a historical document containing a great valuefrom the philosophical, legal and political perspective. The present work is an effort to clarify the sourcesthat lead to the writing of the document. In particular, natural law stands out as a foundation model, andit is emphasized in the analysis of some of the most remarkable thinkers who influenced the ideas theredecanted. This article concludes with the mention of the debates about the sources that led to its writing.